2000
DOI: 10.3133/ofr00442
|View full text |Cite
|
Sign up to set email alerts
|

Titanium mineral resources of the western U.S.: An update

Abstract: Thirteen deposits or districts in the western U.S. have been examined in which titaniummineral resources have been reported or implied. These deposits are of the following general types (in probable order of importance): 1) Cretaceous shoreline placer deposits, 2) silica-sand deposits of California, 3) fluvial monazite placers of Idaho, 4) anorthositerelated deposits, and 5) clay and bauxite deposits of the northwestern U.S. Relative to previous reports, this one shows some greater and some lesser resources (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Of the selected studies shown in Murphy, 1962, 1977;Force, 2000;Force et al, 2001] and in uranium-bearing Mesozoic and Cenozoic sandstones within central U.S. and south Texas [Force et al, 2001]. Looking at the ages and distributions of these deposits in concert with those for the Figure 11.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…Of the selected studies shown in Murphy, 1962, 1977;Force, 2000;Force et al, 2001] and in uranium-bearing Mesozoic and Cenozoic sandstones within central U.S. and south Texas [Force et al, 2001]. Looking at the ages and distributions of these deposits in concert with those for the Figure 11.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…Study of the Ione Formation by the second author was prompted by a need to investigate the heavy-mineral potential, said by Gomes andothers (1979, repeated by Force andLynd, 1984) to be considerable, and by a desire to understand the relation between gold and heavy mineral enrichment (Force, 1991). Some results are published separately by Force and Creely (2000).…”
Section: Economic Contextmentioning
confidence: 99%
“…However, very few papers describe the enrichment of ilmenite in consolidated placers (Faure, 1978;Coipel and Dimanche, 1981; or studies of metamorphosed placers (Muresan, 2002). Although they can represent considerable resources of titanium, such as american Cretaceous shoreline deposits, no specific criteria have been developed to evaluate the effects of metamorphism on titanium oxide-rich metasediments 2000;, Stanaway, 2005. The Sutton paleoplacers have a range of metamorphic titanium oxide phases, presenting an ideal case study of the effects of metamorphism on hemo-ilmenite grains.…”
Section: Economie Applicationsmentioning
confidence: 99%
“…where the liberated ferrous iron is incorporated into chlorite or magnetite . Although the alteration of about one third of the ilmenite grains predates metamorphism (Hébert and Gauthier, in press), any iron released by that process was probably still present in the rocks as cement and thus remained available during metamorphic processes (Force, , 2000. The destabilization of ferromagnesian silicate minerals in the Sutton sandstones also provided iron along with a considerable amount of magnesium .…”
Section: Iron Migrationmentioning
confidence: 99%